การวิเคราะห์ลักษณะทางภูมินิเวศ และ การเปลี่ยนแปลงของภูมินิเวศเมืองชายฝั่งทะเล : กรณีศึกษา เมืองกันตัง จังหวัดตรัง - ญาณิศา ปิยะกมลนิรันดร์ (จุฬาลงกรณ์มหาวิทยาลัย, 2022)
Landscape ecological system of the Trang River Estuary is an area located at the mouth of the river where freshwater from the river and saltwater from the sea mix and blend, creating a complex, dynamic, and biodiverse ecosystem. This is the result of multiple factors working together through time and space, resulting in the formation, processes, and unique characteristics of the Trang River Estuary. It comprises structures, functions, and changes.The objective of this thesis is to understand the changes that occur in the Trang River Estuary, which are caused by both natural and human factors. It serves as a foundation for identifying problems and seeking solutions to the issues that arise in the Trang River Estuary. The study identifies the structure and relationships between the river basin and the estuary, classifies the structure and patterns of the Trang River Estuary, and compares the changes in structure and patterns with land use. The research results demonstrate the unique characteristics of the Trang River Estuary at various scales, including ecosystem services, settlement conditions, and potential for regeneration. These findings form the basis for the planning and management of the Trang River Estuary.